1988
DOI: 10.1063/1.100055
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of high-performance silicon microchannel heat exchangers for laser diode array cooling

Abstract: A heat exchanger package has been demonstrated for semiconductor laser arrays using silicon microstructures with water as the coolant. A thermal impedance of 0.04 °C cm2/W has been achieved for a single linear bar. This design makes use of efficient, edge-emitting laser diode arrays in a rack and stack architecture combined with a high-performance silicon microchannel structure to allow cw operation. The architecture can be scaled to large areas and we project a thermal impedance of 0.09 °C cm2/W for close-pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(13 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Microchannel heat transfer, however, has become increasingly popular and interesting to researchers due to high heat transfer coefficients, with potential for record-high heat transfer coefficient and low to moderate pressure drops when compared to conventional air and liquid cooled systems (Philips 1988;Gillot et al 2000;Hsu et al 1995;Hahn et al 1997;Martin et al 1995;Viday et al 1993). For example, microchannel heat sinks have been demonstrated for high-power laser diode array cooling and have achieved a heat flux removal rate of 500 W/cm 2 (Missaggia et al 1989;Mundinger et al 1988;Beach et al 1992). Figure 1.1 shows the proposed design of a two-phase microchannel heat sink fabricated on the backside of a flip chipbonded IC chip (Zang et al 2003).…”
Section: Prefacementioning
confidence: 99%
“…Microchannel heat transfer, however, has become increasingly popular and interesting to researchers due to high heat transfer coefficients, with potential for record-high heat transfer coefficient and low to moderate pressure drops when compared to conventional air and liquid cooled systems (Philips 1988;Gillot et al 2000;Hsu et al 1995;Hahn et al 1997;Martin et al 1995;Viday et al 1993). For example, microchannel heat sinks have been demonstrated for high-power laser diode array cooling and have achieved a heat flux removal rate of 500 W/cm 2 (Missaggia et al 1989;Mundinger et al 1988;Beach et al 1992). Figure 1.1 shows the proposed design of a two-phase microchannel heat sink fabricated on the backside of a flip chipbonded IC chip (Zang et al 2003).…”
Section: Prefacementioning
confidence: 99%
“…(4) Here Rfi is the thermal resistance between the two channels. If the assumptions are made that a linear regime of heat flow applies and that h is constant with z, it can be shown that the sum of (i) and (2) yields ¶cp d(Ti+T2) 1 dz = (2/RfiJ(T2-Ti).…”
Section: Theorymentioning
confidence: 99%
“…Sakamoto et al [5] increased the total CW output power from 76-120 W by embedding a diamond submount between a AlGaAs/GaAs laser-diode array and a copper heat spreader. 2) Another approach to reducing the thermal resistance is to use convection in microchannels [6], which in the past have been etched into silicon. Missaggia et al [7] mounted GaInAsP/InP buried heterostructure laserdiode arrays on a silicon microchannel heat sink using a solder joint, as depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%